1996
DOI: 10.1159/000121030
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Outcome in Children Treated for Arteriovenous Malformations Using Gamma Knife Radiosurgery

Abstract: Seizures are the second most common presenting symptom of arteriovenous malformations (AVMs) in children. Although radiosurgery has been found to be a safe and effective alternateve treatment, the outcome of seizure control in children after radiosurgery for AVMs is unknown. Between 1987 and 1994, 72 children under the age of 18 years were treated with gamma knife radiosurgery for AVMs at our institution. Fifteen patients (21 %) had seizures as part of their clinical course. There were 11 boys and 4 girls with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
288
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(296 citation statements)
references
References 27 publications
3
288
1
4
Order By: Relevance
“…This finding might be a reflection of the relatively small sample size and larger AVM volumes. Although others have noted that AVM obliteration is not required to improve seizure outcomes, 7,11 prior reports have indicated that seizure reduction is more frequent among those for whom AVM obliteration is acheived. 3,12,34,42,44 Our data also indicate that a history of prior hemorrhage is a negative prognostic factor for seizure improvement.…”
Section: 182728mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding might be a reflection of the relatively small sample size and larger AVM volumes. Although others have noted that AVM obliteration is not required to improve seizure outcomes, 7,11 prior reports have indicated that seizure reduction is more frequent among those for whom AVM obliteration is acheived. 3,12,34,42,44 Our data also indicate that a history of prior hemorrhage is a negative prognostic factor for seizure improvement.…”
Section: 182728mentioning
confidence: 99%
“…1,14 Rates of seizure elimination after SRS for cortical AVMs, regardless of location, range from 50% to 85%. 1,11,23,24 Seizure-free outcomes according to treatment modalities are 78% after microsurgery, 63% after radiosurgery, and 50% after embolization.…”
Section: Factors Associated With Seizuresmentioning
confidence: 99%
“…For the final quantitative analysis, we identified 19 series comprising 1104 patients with AVMs and seizures who underwent SRS. 2,13,16,20,22,33,34,37,39,41,43,48,57,58,63,64,69,71,73 Figure 1 shows a flow chart of the review process.…”
Section: Literature Searchmentioning
confidence: 99%
“…33,41,69,71 However, this association was found to be nonsignificant in 4 other studies. 22,37,39,57 Relationships between seizure characteristics and seizure outcomes following SRS were also inconsistent; complex partial seizures with or without secondary generalization, generalized tonic-clonic seizures, infrequent and shortduration seizures, and seizure frequency have been associated with improved seizure control. 16,33,39,57,71 In contrast, other studies have also found no significant relationship between seizure outcome and seizure type, duration, frequency, and pattern or age at seizure onset.…”
Section: Obliteration and Other Factors Related To Seizure Outcomementioning
confidence: 99%
“…29 Another AVM radiosurgery study of 15 pediatric patients with seizures at presentation did not find obliteration to be associated with seizure outcomes. 22 Additionally, Schauble et al reported on a series of 65 patients with AVM-associated seizures who underwent radiosurgery without a significant association between obliteration and seizure control. 42 Engel Class I outcomes were observed in 78% of patients.…”
Section: Effect Of Radiosurgery On Seizures Outcomes For Patients Witmentioning
confidence: 99%